Black Sea, grain, and two humanitarian corridors: unblocking Ukrainian shipping amid the Russian invasion - Кормич, Борис Анатолійович; Кормич, Б. А.; Kormych, Borys A.; Аверочкіна, Тетяна Володимирівна; Аверочкіна, Т. В.; Averochkina, Tetiana V.; Кормич, Людмила Іванівна; Кормич, Л. І.; Kormych, Liudmyla I. (London : Taylor & Francis, 2024)
Since the start of the full-fledged Russian invasion, Ukraine has attempted twice to unlock its Black Sea ports, both of which took place after significant changes during hostilities. The initial attempt, the Black Sea Grain Initiative of 2022–2023, facilitated by the UN, employed mediation techniques from the hybrid stage of the conflict 2014–2022. The unilateral humanitarian corridor (since 2023) relied on Ukraine’s military capabilities to prevent Russia from interfering with neutral shipping. This was combined with the efforts of international partners and businesses. The article examines the advantages and disadvantages of each approach to ensuring neutral shipping in conflict zones.
Kormych B. Black Sea, grain, and two humanitarian corridors: unblocking Ukrainian shipping amid the Russian invasion / B. Kormych, T. Averochkina, L. Kormych // Small Wars and Insurgencies. – London : Taylor & Francis, 2024. – 35(8). – P. 1360 - 1396. URL: https://doi.org/10.1080/09592318.2024.2384679
Keywords: Ukraine; Russia; armed conflict; Black Sea; blockade; merchant shipping